(untitled) (INNOVATIVE ECONOMY, 2026)
Rymar O.H. SUPPORT OF INNOVATIVE STARTUPS THROUGH THE PRISM OF FINANCIAL MECHANISMS Purpose. The aim of the article is a comprehensive theoretical and practical study of financial mechanisms for supporting innovative startups, determining their significance and features of application at different stages of startup development, as well as generalizing international and domestic experience in financing innovative entrepreneurship in order to substantiate the directions of its further development. Methodology of research. The article applies a set of general scientific and special research methods, including the method of system analysis ‒ to generalize theoretical approaches to the financial support of innovative startups; methods of comparison and scientific generalization ‒ to study modern financial mechanisms for stimulating startup ecosystems; statistical and analytical methods ‒ to assess trends in the development of innovative entrepreneurship; and the method of logical generalization ‒ to formulate conclusions and practical recommendations for improving the financial support of innovative startups. Findings. The essence and peculiarities of financial mechanisms for supporting innovative startups have been determined, their comparative analysis has been carried out, and the influence of each mechanism on the development of startup projects has been identified. The advantages and weaknesses of the main sources of startup financing, including venture capital, grant support, crowdfunding, business angel investment, and state programs for stimulating innovation activity, have been revealed. The foreign experience of leading countries in the field of financial support for innovative startups has been studied, and the most effective instruments for stimulating innovative entrepreneurship have been identified. Directions for improving the financial support of innovative startups in Ukraine have been proposed, taking into account international practices and current trends in the development of the innovation economy. Originality. The theoretical and methodological principles of supporting innovative startups through a system of financial mechanisms have been deepened and directions for improving their financial support in the conditions of transformation of the modern economy have been substantiated. Vectors for optimizing the support system for innovative enterprises in Ukraine have been determined, based on the adaptation of the international experience of the Horizon Europe, SBIR and Innovate UK programs, the development of venture financing, the activation of state incentives and the development of the institutional infrastructure for supporting startup projects. Practical value. The obtained research results can serve as a basis for further regulatory decisions and strategies for the development of domestic startup projects under the conditions of rapid changes and challenges in the economy of Ukraine and the world. Key words: innovative startups, financial mechanisms, venture capital, private investments, crowdfunding, business angels, state programs.